KURANGI EMESIS GRAVIDARUM DENGAN AROMA JERUK NIPIS - Zakkiyatus Zainiyah; Dwi Wahyung tiyas (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Emesis gravidarum is vomiting in pregnant women (Medical Dictionary). This situation is usually preceded by nausea (Nausea). In the United States and Canada between 400,000 and 350,000 pregnant women experience the incidence of nausea and vomiting each year in Western countries and urban dwellers. According to Hernawati, et al. (2014) in Indonesia, there are 69.2% of pregnant women who experience nausea and vomiting and 30.8% do not experience nausea and vomiting during pregnancy, from 52 samples taken. Based on a survey through interviews conducted on 2 pregnant women at PMB Masrufah, SST, Jaddih, Bangkalan, said that their nausea and vomiting would be reduced when using kissed lime. The method used to carry out community service is by collecting data on the number of pregnant women in PMB Masrufah, SST, Jaddih, then conducting interviews with mothers about understanding nausea and vomiting and handling nausea and vomiting, then making a time contract with the mother. The activity was continued with nausea and vomiting counseling, training in the management of nausea and vomiting by giving the aroma of lime which was held at PMB Masrufah, SST, Jaddih. Participants in the activity were 35 pregnant women but there were 20 pregnant women who experienced emesis gravidarum at PMB Masrufah, SST, Jaddih, Bangkalan who participated in the training activity of giving lime aroma to pregnant women with nausea and vomiting. While participating in the activity, the mother was very enthusiastic about the material presented. The mother was also able to demonstrate the aroma therapy of lime. The result of the activity is a decrease in the intensity of nausea and vomiting after being given lime aroma therapy.